Sampling of populations : methods and applications - Levy, Paul S.; Lemeshow, Stanley (New York : Wiley, 1999)
Now in its third edition, this sampling text continues to provide a readable, practical treatment of the subject. Keeping the mathematics to a minimum, it walks the reader through real-world sample surveys - from sampling designs to problems of missing data and nonresponse to estimation procedures.
"Wiley-Interscience publication."
Includes bibliographical references and index.
oif 07/04/15
Loan
Keywords: Sampling (Statistics); Population -- Statistical methods